Tantangan Pembelajaran Proyek Citizen Science di Indonesia - Gusti, Utari Akhir; Hidayat, Topik; Sriyati, Siti (Yayasan Indonesia Bermutu, 2025)
The purpose of this research is to provide information about the challenges of citizen science project learning in Indonesia, so that its implementation is maximized. The research method used is descriptive qualitative. Data collection was conducted through interviews, observations, and literature review. The researcher used data triangulation which aims to increase the researcher's understanding of the data and facts. This local community engagement learning provides enormous benefits in school learning. The advantages of this learning are the involvement of experts and non-experts in the learning process, students learn from real objects, produce various products, and increase knowledge and skills. In addition, the disadvantages of this learning require additional time in the learning process. Challenges in citizen science project learning include cohesiveness or closeness of learners, interpersonal communication, use of information technology, and time. Thus, citizen science project learning is one of the current learning innovations that can be applied by teachers in schools.